Management‐Employee Alliance and Earnings Opacity* - Khurana, Inder K.; Zhong, Rong (Irene) (Contemporary Accounting Research, 2023)
ABSTRACT The rise of stakeholder governance has triggered a wave of legal initiatives to strengthen the employee voice in firms. However, how managers trade off the competing objectives between shareholders and employees when making financial reporting decisions is not well understood. Exploiting staggered employment protection laws (EPLs) across 26 countries, we find that managers facing strong EPLs report more opaque earnings. Exploring the mechanism, we show that EPLs induce manager‐employee alliance: EPLs enhance employees' power to influence managers' private benefits and create an incentive for managers to treat employees more favorably, leading to an increase in manager‐employee reciprocal benefits. Further analysis shows that the alliance drives the increase in opacity following EPLs. Such alliance‐induced opacity impedes the ability of institutional shareholders to make timely adjustments to portfolio holdings in response to EPLs. Last, we identify several governance mechanisms that help break the manager‐employee nexus and restore reporting transparency. Overall, our study documents manager‐employee alliance as a potential cost of rigid labor laws and an important source of managerial reporting bias.